2005
DOI: 10.1007/bf03395505
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Test Order and Nodal Distance on the Emergence and Stability of Derived Discriminative Stimulus Functions

Abstract: The present study examined the effects of equivalence test order and nodal distance on the emergence and stability of derived discriminative stimulus functions. Participants in 1 group were exposed to a transfer of functions test foillowing a symmetry and equivalence test, another group of participants completed a symmetry and equivalence test following a transfer test, and a final group of participants received a symmetry test only if they failed to demonstrate immediate transfer, after which time they were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
9
0
4
Order By: Relevance
“…indeed, future studies might further examine this robustness by testing for derived avoidance across a greater number of probe trials. the long-term stability or maintenance of derived transformation also warrants further attention (see rehfeldt & Dymond, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…indeed, future studies might further examine this robustness by testing for derived avoidance across a greater number of probe trials. the long-term stability or maintenance of derived transformation also warrants further attention (see rehfeldt & Dymond, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…During this time gap, participants did not have additional training or testing (e.g., Rehfeldt & Hayes, 2000;Saunders, Wachter, & Spradlin, 1988;Spradlin, Saunders, & Saunders, 1992;Wirth & Chase, 2002). Rehfeldt and Dymond (2005), however, reported that transfer of functions, a phenomenon related to stimulus equivalence, in the sense that functions acquired directly by one class-member transfer to other class-members, showed considerable less stability when retested after 1 month.…”
mentioning
confidence: 99%
“…However, if transitivity is one of the properties defining the emergence of equivalence, and the route proposed here for the emergence of transitivity is accurate, then transfer of stimulus functions cannot be characterized as merely a consequence of the emergence of equivalence; rather, it must be present prior to and be involved in the emergence of equivalence. As evidence in support, Rehfeldt and Dymond () showed that transfer of functions may be present among stimuli related in baseline without explicit testing for the emergence of symmetry and transitivity; however, in that study, for those participants who failed to display transfer of functions, transfer appeared after testing for symmetry.…”
Section: Discussionmentioning
confidence: 80%